A head for dispensing an elastomeric mix onto a manufacturing line conveyor - Kozioł, Stanisław; Matecki, Krzysztof; Samborski, Tomasz; Zbrowski, Andrzej; Bąba, Grzegorz (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
The prototype of a dispensing head of thermoplastic elastomers was designed and construct-ed at the Institute for Sustainable Technologies for a purpose-built manufacturing line for producing textile-elastomer composite glues. The elastomer dispensing head enables the transfer of the elastomer onto the moving material; it evens out the applied layer or creates discontinuous layers which are permeable for water vapour or air. The device heats the me-dium being dispensed using an oil heated conduit or electric heating elements with tempera-ture control. This design is capable of changing the flow direction of the substrate in the manufacturing line, regulating a precise layer thickness, automatically executing setup and maintenance, and safe handling. Using the dispensing head constructed as part of project developing the manufacturing, the BOCHEMIA company has developed innovative solutions for manufacturing technologies of multifunctional composites of innovative materials which exhibit the following properties: energy absorbing (which provided impact absorption properties), fungicidal, and bactericid-al. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)